Some Convergence Theorems for Henstock-Kurzweil Integrable Functions with Values in Riesz Spaces Defined on Euclidean Spaces - Muslim Ansori (Jurnal Matematika, Statistika dan Komputasi, 2007)
Some convergence Theorems for Henstock Integrable functions from Euclidean space  into Riesz spaces are constructed by using decreasing net of double sequences. We give more general results than those of the convergence Theorems for Henstock Integrable functions with values in sequence spaces.